Bioanalysis of aminoglycosides using high-performance liquid chromatography - Seth K. Amponsah; Joseph A. Boadu; Daniel K. Dwamena; Kwabena F.M. Opuni (International Association of Physical Chemists (IAPC), 2022)
Aminoglycosides are broad-spectrum antibiotics used in the treatment of gram-negative bacterial infections. Due to their nephrotoxic and ototoxic potential (narrow therapeutic index), the use of aminoglycoside for clinical indications requires monitoring. The objective of this review was to identify relevant literature reporting liquid chromatographic methods for the bioanalysis of aminoglycosides in both preclinical and clinical settings/experiments. Data on liquid chromatographic methods were collected from articles in an online academic database (PubMed, Science Direct, Scopus, and Google Scholar). All 71 articles published from 1977 to 2020 were included in the review. Reversed-phase liquid chromatography was the most used method for the bioanalysis of aminoglycosides. Fluorescence or ultraviolet detection methods were mostly used from 1977 to 2002 (51 articles), while mass spectrometry was predominantly used as a detector from 2003 to 2020 (15 articles). Sixty-seven articles reported calibration ranges, which varied significantly for the various drugs assayed: some in the range of 0.1-0.5 ng/mL and others 1250-200000 ng/mL. Also, 61 articles reported R2 values (0.964-1.0) for almost all analytes under consideration. Sixty-three articles reported percent recoveries mostly between 61.0 % to 114.0 %, with only two articles reporting recoveries of 4.9 % and 36 %. Out of the 71 reviewed articles, 56 reported intermediate precision values ranging between 0.331 % to 19.76 %, which is within the acceptable limit of 20 %. This review will serve as a guide for research and/or routine clinical monitoring of aminoglycosides in biological matrices.